End of Life Decisions: The extent to which quality of life factors should affect them - Mokuolu, Toluwani Ayobami (Kent Law Review, 2017)
The significance of quality of life factors in end of life decisions cannot be overstressed. However, a plethora of case law shows that there are other factors which must be considered. The landmark cases of W v M and Others[1] and Airedale N.H.S Trust v Bland[2] indicate that autonomy and best interests of the patient must be given adequate consideration before making end of life decisions. The courts held that despite M’s minimally conscious state, dying was not in her best interests. However, in Bland where he had been in a persistent vegetative state, it was held that it was lawful for treatment to be withdrawn. This article gives a critical assessment of the disparities in both decisions and with the aid of other case law, examines the extent to which quality of life factors have influenced the decisions of the courts. Furthermore, it argues whether patient autonomy should override best interests and then it concludes that quality of life factors should influence end of life decisions to the extent of the patient’s autonomy or self-determination. In other words, quality of life factors must be considered but respect for patient autonomy should be paramount. * LLM Medical Law and Ethics Candidate, Kent Law School, University of Kent, tam36@kent.ac.uk [1] [2011] EWHC 2443 (Fam). [2] [1993] AC 789 (HL).